Using Antimicrobial Photodynamic Therapy with Ultrasound Devices and Bioactive Glasses as a Combined Approach for Treating Dentin Caries Lesions - Besegato, João Felipe [UNESP]; Melo, Priscila Borges Gobbo de [UNESP]; Abreu Bernardi, Adilson César; Souza, Marina Trevelin; Zanotto, Edgar Dutra; Bagnato, Vanderlei Salvador; de Souza Rastelli, Alessandra Nara [UNESP] (MDPI, 2023)
Novel approaches for caries lesion removal and treatment have been proposed. This study evaluates the combined use of an experimental ultrasound, aPDT (antimicrobial photodynamic therapy) and bioactive glasses on the removal, decontamination and remineralization of dentin caries lesions. A biological model created with a duo species biofilm (Streptococcus mutans and Lactobacillus acidophilus) was used for the development of a caries-like lesion over the dentin for 7 days. Bovine dentin specimens (4 × 4 × 2 mm) were randomized according to the following caries removal techniques: bur (BUR) or ultrasound (ULT), decontamination (with or without aPDT) and remineralization materials (45S5 or F18 bioactive glasses). The following different groups were investigated: caries lesion (control); sound dentin (control); BUR; BUR + aPDT; ULT; ULT + aPDT; BUR + 45S5, BUR + F18; ULT + 45S5; ULT + F18; BUR + aPDT + 45S5; BUR + aPDT + F18; ULT + aPDT + 45S5; and ULT + aPDT + F18. Transverse microradiography (TMR), cross-sectional microhardness (CSH), FT-Raman spectroscopy and confocal microscopy (CLSM) were performed. A two-way ANOVA and Tukey’s test were used (α = 0.05). (3) Results: The TMR revealed a lesion depth of 213.9 ± 49.5 μm and a mineral loss of 4929.3% vol.μm. The CSH increases as a function of depth, regardless of the group (p < 0.05). Removal with BUR (24.40–63.03 KHN) has a greater CSH than ULT (20.01–47.53 KHN; p < 0.05). aPDT did not affect the CSH (p > 0.05). No difference was observed between 45S5 or F18 (p > 0.05), but a change was observed for ULT (p > 0.05). The FT-Raman shows no differences for the phosphate (p > 0.05), but a difference is observed for the carbonate and C-H bonds. The CLSM images show that aPDT effectively inactivates residual bacteria. A combination of ULT, aPDT and bioactive glasses can be a promising minimally invasive treatment.
Keywords: biofilm; caries removal; dental caries